Characterization Of A Highly Active Polyhydroxyalkanoate Synthase - Chuah, Jo-Ann (2012)
Polyhydroxyalkanoate (PHA) synthase from a locally isolated Chromobacterium sp. USM2 (PhaCCs) exhibited superior polymerizing ability and broad in vivo substrate specificity with preferences for short chain length (SCL) [3-hydroxybutyrate (3HB) and 3-hydroxyvalerate (3HV)] and medium chain length (MCL) [3-hydroxyhexanoate (3HHx)] monomers. For further characterization of the synthase, a Strep2-tagged PhaCCs for expression in and purification from Escherichia coli, was constructed in this study. In vitro enzymatic assay revealed an activity of 253 ± 13 U/mg for polymerization of 3-hydroxybutyryl-coenzyme A (3HB-CoA), which was approximately fivefold higher than that of model PHAproducing strain Cupriavidus necator (39 ± 5 U/mg).